Efficacy of Target Drug Delivery and Dead Space Reduction Using Antibiotic-loaded Bone Cement for the Treatment of Complex Spinal Infection. Issue 9 (November 2017) - Masuda, Soichiro; Fujibayashi, Shunsuke; Otsuki, Bungo; Kimura, Hiroaki; Matsuda, Shuichi
Abstract : Study Design: A retrospective study. Objectives: We have treated complex cases of surgical site infection (SSI) successfully using antibiotic-loaded bone cement to avoid the need for implant removal. In the present study, we describe a new treatment option for SSI. Summary of Background Data: Although there are several treatment options for SSI after spinal surgery involving instrumentation, several types of problems may arise and are difficult to cure. Materials and Methods: Eleven patients with SSI after undergoing spinal surgery involving instrumentation were studied. All had been refractory to conventional treatments, including intravenous antibiotic administration and conventional debridement and irrigation. Antibiotic-loaded bone cement was placed on and around the instrumentation to cover them and to occupy the surrounding dead space. Two general types of antibiotics were loaded into the polymethylmethacrylate bone cement. The recipes for the mixture were changed depending on the bacterial cultures. Sensitive antibiotics were administered generally for 2–6 weeks until the C-reactive protein level was normalized. Results: All patients were treated successfully using antibiotic-loaded bone cement. Only 1 patient needed a repeat of this procedure to treat an infection. Antibiotic-loaded bone cement was placed in situ in all patients during the follow-up period and there were no significant adverse events. Conclusions: Antibiotic-loaded bone cement treatment reduces the dead space and achieves the targeted drug delivery simultaneously. Treatment using antibiotic-loaded bone cement is an effective treatment option for complex spinal SSI.